The pathological and molecular genetic landscape of the hereditary renal cancer predisposition syndromes. Issue 1 (11th April 2022) - Al‐Obaidy, Khaleel I; Alruwaii, Zainab I; Williamson, Sean R; Cheng, Liang
Abstract : It is estimated that 5–8% of renal tumours are hereditary in nature, with many inherited as autosomal‐dominant. These tumours carry a unique spectrum of pathological and molecular alterations, the knowledge of which has expanded in recent years. Due to this knowledge, many advances in the treatment of these tumours have been achieved. In this review, we summarize the current understanding of the genetic renal neoplasia syndromes, clinical and pathological presentations, molecular pathogenesis, advances in therapeutic implications and targeted therapy. Abstract : In this review, we summarize the current understanding of the genetic renal neoplasia syndromes, the clinical and pathologic presentations, their molecular pathogenesis, the advances in therapeutic implications and targeted therapy.